Peningkatan Literasi Pengelolaan Keuangan Melalui Event BERANDA X OJK 2023 - Nabiilah Rizky Auliya; Imam Syafganti; Muhammad Iqbal Katik Rajoendah; Annisa Wardhani; Yuningsih Yuningsih (Bisnis Event, 2026)
Financial literacy is a fundamental necessity that everyone should possess to avoid financial issues. The Financial Services Authority (Otoritas Jasa Keuangan) is endeavoring to expand its financial literacy campaign program aimed at educating and enhancing the financial literacy of the community, with the current primary target being Housewives. Efforts supporting the Financial Services Authority's program to achieve this goal include socialization through the organization of the talk show event "Beranda (Belajar Antar Bunda)". To achieve this objective, the approach involves organizing the talk show event and conducting research using observation methods and questionnaires among the participants of the talk show event. The results of this research indicate that the "Beranda" talk show event was successfully conducted, as it provided benefits in financial management and significantly increased knowledge and awareness of financial literacy among the participants of the "Beranda" talk show event.